Islamic Education Management Students' Strategies in Managing Time Between Lectures, Organizations, Boarding Students, And Part-Time Work - Wardatul Jannah; Rahma Syifa Fauziyah; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
Students of Islamic Education Management (MPI) who undertake multiple roles, such as studying while boarding at pesantren, working part-time, or participating in organizations, face challenges in balancing academic and non-academic responsibilities. This study aims to describe the time management strategies of MPI students in balancing lectures with other activities and their impact on academic achievement. A qualitative descriptive approach was employed, with data collected through semi-structured in-depth interviews with three key informants: Nenti (lectures + boarding), Siti Fatonah (lectures + part-time work), and Aleni Frisiliani (lectures + organizations). Data were analyzed using Miles and Huberman’s (1994) model through data reduction, presentation, and conclusion drawing, supported by source triangulation. The findings reveal that the informants applied time management strategies based on academic priorities, time segmentation, to-do lists, ask chunking, proactive communication, and social support from family, peers, lecturers, and organizational or boarding administrators. These strategies effectively maintained focus, prevented burnout, and ensured consistently high Grade Point Averages (GPA >3.85). The study confirms that multiple roles do not inherently reduce academic performance; rather, they can foster discipline, independence, and holistic competence when time management strategies are properly implemented